Dynamic structural states of ClpB involved in its disaggregation function - Takayuki Uchihashi (Nature Portfolio, 2018)
The bacterial protein disaggregation machine ClpB uses ATP to generate mechanical force to unfold and thread its protein substrates. Here authors visualize the ClpB ring using high-speed atomic force microscopy and capture conformational changes of the hexameric ring during the ATPase reaction.